Pole Allocation Applied to Two Buildings Connected by Joint Damper - Yoshiki Ikeda; Yuki Matsumoto (Shock and Vibration)
For two adjacent buildings connected by a joint damper, an inverse problem is formulated based on the pole allocation method in control theory. The structural system is simplified as a two-degrees-of-freedom (2-DOF) lumped-mass damped shear model. The unified governing equation, which expresses the relationship between an assigned control target and the structural parameters for an earthquake-resistant building, seismically isolated building, or passively controlled building, is extended to structural control using a joint damper. The introduced equation automatically constrains the variations in the structural parameters under the assigned modal properties. The integration of the pole allocation method and fixed-point theory directly estimates the additional damping effect on the target buildings from the optimum capacity of the joint damper, which improves the trial-and-error steps at the preliminary design stage. The past fixed-point theories do not provide the additional damping effect but the optimum damping coefficient of the joint damper. The present study directly links the additional damping with the damping of the joint damper. Numerical examples are used to verify the theoretical integration using a 20-DOF building model wherein two 10-DOF models are connected by a joint damper between the top lumped masses.